PERSEPSI PELAKU UMKM DESA PEMATANG SERAI KABUPATEN LANGKAT TERHADAP LEMBAGA KEUANGAN MIKRO SYARIAH - Heriyati Chrisna; Hernawaty Hernawaty; Noviani Noviani (Jurnal Abdi Ilmu, 2022)
This study aims to determine how the perception of UMKM in the village of Pematang Serai Tanjung Pura District Langkat Regency on Syariah Microfinance Institutions (LKMS). This research is descriptive research with a qualitative approach. The data collection technique is in the form of primary data consisting of documentation, interviews, and questionnaires. Questionnaires were distributed to 12 UMKM in the village of Pematang Serai. Samples as many as 12 people were chosen because indeed the number of UMKM players who were members of the Pucuk Lemonger's UMKM community were only 12 people because they were only formed by several time ago. The results showed that the perpetrator of the UMKM of the village of Pematang Serai Village included in the category that was still not good / low because UMKM players were still not so understanding the characteristics and services provided by sharia financial institutions. They still assume that this syariah microfinance institution is almost the same as conventional bank financial institutions that apply high interest so that they are afraid of the risks caused if they cannot afford loans. It is necessary to socialize from universities, especially the Pancabudi Development University to provide an understanding of them related to Islamic microfinance institutions to resolve the issue of business capital in particular